Driving Sustainable Business Transformation through Young Professionals: The SDG Innovation Accelerator 2025 in Indonesia - Ririn Breliastiti; Steven Lazaurus Alfianus (Indonesian Journal of Business Analytics, 2025)
The Sustainable Development Goals (SDGs) provide a global roadmap for coordinated solutions across social, environmental, and economic domains. This study analyzes the 2025 SDG Innovation Accelerator (SDGI) in Indonesia, organized by the Indonesia Global Compact Network and BRIN, which engaged 94 young professionals from 20 companies to generate SDG-aligned innovations. Using a descriptive qualitative approach and secondary data, the study highlights the case of PT Singaland Asetama’s award-winning 'Green Carbon Black' and projects other plausible outcomes. Findings emphasize the role of multi-stakeholder collaboration, capacity building, and global exposure in fostering sustainability-oriented innovation, with implications for policy, corporate practice, and future accelerator design.